Investigation of indoor bioaerosol pollution and its source from ACMV system in Singapore - Oh, Jun Wei (Nanyang Technological University, 2021)
Singapore is a hot and humid country where people depend heavily on air-conditioning to suit their thermal comfort by controlling the indoor temperature. There is a large usage of Air Conditioning and Mechanical Ventilation (ACMV) systems in Singapore. ACMV systems are mainly operated within office buildings, schools or in the shopping malls. As much as ACMV system operates to improve indoor thermal comfort, it is possible that ACMV system could emit poor quality of air. Furthermore, bioaerosol could be a potential source of ACMV system. Emission of bioaerosol from ACMV system will contribute to indoor pollution and exposure to bioaerosol will bring detrimental health effects such as respiratory diseases or infectious disease. Moreover, people spend most of their time indoor and therefore this study will serve to investigate indoor bioaerosol pollution and its sources from ACMV system.